2020
DOI: 10.1002/adma.201907690
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Metal‐Free Electrocatalyst of F‐Doped Porous Carbon toward N2 Electroreduction

Abstract: N2 electroreduction into NH3 represents an attractive prospect for N2 utilization. Nevertheless, this process suffers from low Faraday efficiency (FE) and yield rate for NH3. In this work, a highly efficient metal‐free catalyst is developed by introducing F atoms into a 3D porous carbon framework (F‐doped carbon) toward N2 electroreduction. At −0.2 V versus reversible hydrogen electrode (RHE), the F‐doped carbon achieves the highest FE of 54.8% for NH3, which is 3.0 times as high as that (18.3%) of pristine ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(87 citation statements)
references
References 46 publications
1
86
0
Order By: Relevance
“…Considering Lewis acidity of H + ion (or a proton), Liu et al introduced F atoms into 3D porous carbon framework to generate Lewis acidic sites in the material, via electron modulation, that can repel a proton and limit its binding on the material. [ 106 ] NH 3 temperature‐programmed desorption (NH 3 ‐TPD) proved the presence of a much higher density of Lewis acidic sites in the F‐doped carbon than in the pristine carbon. DFT calculations revealed that F‐containing graphene model possessed a higher energy barrier for H 2 evolution as well as a lower energy barrier for N 2 adsorption and dissociation than the F‐free counterpart.…”
Section: Porous Nrr Electrocatalystsmentioning
confidence: 99%
“…Considering Lewis acidity of H + ion (or a proton), Liu et al introduced F atoms into 3D porous carbon framework to generate Lewis acidic sites in the material, via electron modulation, that can repel a proton and limit its binding on the material. [ 106 ] NH 3 temperature‐programmed desorption (NH 3 ‐TPD) proved the presence of a much higher density of Lewis acidic sites in the F‐doped carbon than in the pristine carbon. DFT calculations revealed that F‐containing graphene model possessed a higher energy barrier for H 2 evolution as well as a lower energy barrier for N 2 adsorption and dissociation than the F‐free counterpart.…”
Section: Porous Nrr Electrocatalystsmentioning
confidence: 99%
“…Meanwhile, the electronic structure of the local carbon skeleton would have a significant change in the potassium storage behavior. The F dopants are usually successfully doped into carbon skeleton by direct heat treatment of F‐containing precursors, such as polyvinylidene fluoride (PVDF) and poly‐tetrafluoroethylene (PTFE), or posttreatment of HF etching 71,72 . NH 4 F, through mixing with the carbon sources and further pyrolyzing the mixture under inert atmosphere, was also found to be an effective F dopant 73 …”
Section: Defective Carbon For Potassium‐ion Batteriesmentioning
confidence: 99%
“…6,7 To realize a green and sustainable strategy for N 2 xation, electrochemical reduction of N 2 has recently attracted much attention, being an environmentally friendly route involving mild conditions. [8][9][10] To date, a number of catalysts have been developed for the NRR, including noble metals, [11][12][13] transition metals, 14,15 metalfree materials, [16][17][18] metal-C composite materials [19][20][21] and Au-Fe 3 O 4 . 22 These catalysts have demonstrated potential applications in the NRR with improved FE and NH 3 yield.…”
Section: Introductionmentioning
confidence: 99%